Performance Evaluation of Granite Dust, Dolerite Dust and Woodash as Additivies on the Lateritic Soil of Sagamu-Papalanto Southwestern Nigeria and its Implication for Road Construction (Global Journal of Science Frontier Research, 2021)
The study focuses on evaluating the performance of granite dust, dolerite dust and wood ash as additive on the lateritic soil of Sagamu-Papalanto south western Nigeria. The soil was studied under varying proportions of the additives. The mineralogical composition of the soil and additives were analyzed using X-ray diffraction and X-ray fluorescence methods. The geotechnical properties of the soil such as grain size distribution, consistency limits test, specific gravity, compaction, California bearing ratio (CBR) test and unconfined comprehensive test (UCS) were conducted on the natural soil and the additives at varying percentage proportions. The results from the investigation revealed a reduction in the plasticity index, linear shrinkage, and improvement in the compaction properties and an enhancement in the shear strength property of the soil. It is was concluded from the study that at 24% addition of the granite dust, the UCS of the soil acquired an adequate strength to meet the Nigerian specification requirements for road construction as subbase and base course.
Keywords: soil; waste; road; sagamu-papalanto; wood ash; dolerite dust; granite dust; geotechnical